Dietary protein requirements for tambaqui Colossoma macropomum (Cuvier, 1818) juvenile - Amancio, Alda Lúcia; Silva Neto, Manuel; Jordão Filho, José; Fonseca, Sthelio; Silva, José Humberto (Revista Ciência Agronômica, 2019)
The freshwater fish, tambaqui, Colossoma macropomum, is a native species of Brazilian fauna that has the potential to become a widespread aquaculture species, howerer, studies regarding the nutrient requirements remain scarce, often producing conflicting results. Hence, the currently available information is insufficient to formulate the specific diet of this species, for the different growth stages. This study aimed to evaluate the effects of dietary crude protein levels on the growth performance, body composition and ammonia excretion rates in tambaqui of 2–20 g body weight. Juvenile (average weight, 1.70 ± 0.05 g) were fed four times a day over a 60 days period using diets containing 300; 350; 400 and 450 g kg-1 crude protein in a completely randomized experimental design. The tambaqui juvenile fed diet containing 300 g kg-1 crude protein exhibited higher feed intake, specific growth rate, protein efficiency ratio, and protein productive value. This finding shows an improvement in protein utilization efficiency when fish are fed the lowest level of this nutrient in the diet; however, more viscero-somatic fat deposition and body lipid content was observed in these fish. The total ammonia excretion rates were lower in tambaqui fed diet containing 300 g kg-1 crude protein than those fed diets containing 450 g kg-1 crude protein. From the present investigation, it can be conclude that 300 g kg -1 crude protein should be fed to tambaqui juvenile of 2–20 g body weight.